How Adult Gamers Perceive Their Learning When Playing Video Games for Enjoyment : A Narrative Inquiry - Nassrallah, Jihan (Université d'Ottawa / University of Ottawa, 2023)
The value of video games in education has been displayed in more than one field (Gee, 2007; Devlin, 2011). The possible effects of using video games as a learning tool have been studied in numerous academic situations: with young students ranging from elementary to secondary levels (Barab et al., 2009; Cipollone, 2015; Kellert, 2018; Seidel et al., 2019; Sherry et al., 2019; Tüzün et al., 2019), with postsecondary students (Mahood & Hanus, 2017; Smith et al., 2020; Vásquez & Ovalle, 2019), and with educators employing video games in the classroom (Bell & Gresalfi, 2017). The purpose of this study was to investigate how adult gamers perceive their learning when playing video games for enjoyment. To conduct this study, Barbara Rogoff's interpretation of sociocultural theory (2003) was adopted, which offers a closer look on the influences of cultural communities. This study recruited a sample size of 6 adult gamers and adopted a narrative inquiry model, allowing participants to share their lived experiences about video game play and everything related to it. The results indicate that what participants were learning during their video game play could fall under one or more of these four themes: wellbeing, problem-solving, transferable skills, and multimedia literacy. By understanding how video games function as an inherent learning tool, this study helps create a foundation for future research in the field.
Keywords: video games; learning; adult learning